Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1002/poi3.158
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Platform Effects in Online Discussions

Abstract: Online discussions are the essence of many social platforms on the Internet. These platforms are receiving increasing interest because of their potential to become deliberative spaces. Many studies have proposed approaches to measure online deliberation and to evaluate which are the best design principles for deliberative online platforms. However, little research has focused on how deliberation in online platforms is affected by the arrival of events like the emergence of new topics or the modification of pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 61 publications
1
16
0
1
Order By: Relevance
“…The combination of both approaches makes Decidim Barcelona an interesting case study for multiple reasons. First, recent studies have shown that conversation threading in online discussion platforms promotes the emergence of discussion cascades with higher levels of reciprocity [3] and online deliberation [5]. Second, given that users are able to mark the alignment of comments with the proposal (positive, negative and neutral), we can compare the typical network structures originated by the different types of comment alignment.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of both approaches makes Decidim Barcelona an interesting case study for multiple reasons. First, recent studies have shown that conversation threading in online discussion platforms promotes the emergence of discussion cascades with higher levels of reciprocity [3] and online deliberation [5]. Second, given that users are able to mark the alignment of comments with the proposal (positive, negative and neutral), we can compare the typical network structures originated by the different types of comment alignment.…”
Section: Introductionmentioning
confidence: 99%
“…Additive decomposability is a structural property of some inequality measures requiring that for any partition G of the population into groups, the measure, I (y), can be expressed as the sum of a "within-group component" I G ω (y) (a weighted sum of subgroup inequality levels) and a "between-group component" I G β (y) (computed by assigning to each element in a subgroup д ∈ G the subgroup's mean benefit µ д ): 2 I (y) = I ω (y) + I β (y). Following [30], we focus on a family of inequality indices called generalized entropy indices that satisfy additive decomposability.…”
Section: Decomposable Measures Of Inequalitymentioning
confidence: 99%
“…To this end, prior works have proposed Regression Discontinuity Designs (RDDs) [2,11,17,21]-a quasi-experimental design that reasons about the causal effects of interventions by identifying a threshold above or below which an intervention is assigned. We follow this methodology by comparing the projects before and after a new design feature is introduced.…”
Section: Evidence On the Impact Of Nudgesmentioning
confidence: 99%
“…Kaltenbrunner, González, Ruiz de Querol and Volkovich (2011), from a more sociological point of view, studied the behaviour of Menéame users when sharing websites between December 2005 and July 2009, and they concluded that it promotes interaction not only among friends but also that users are more motivated to share content than to establish relations of friendship, which could have positive implications for the design of a networked community. Aragón, Gómez and Kaltenbrunner (2017) detected that a change in the interface used by Menéame to show discussions caused a significant increase in debate among users. No other research has been carried out regarding the aggregator that is being studied in this paper.…”
Section: The Appearance Of News Aggregatorsmentioning
confidence: 99%